PERANCANGAN USER INTERFACE PADA WEBSITE STREAMING ANIME MENGGUNAKAN APLIKASI FIGMA - Adhitama, Adam; Widiyaningsih, Wiwied; Lailasari, Mita (Jurnal Nasional Teknologi Komputer, 2022)
Videos and Japanese cartoons called anime are getting more and more fans. With the development of computer technology, internet, to be able to watch movies and videos, it is enough to look at streaming websites. To create an attractive anime streaming website that provides various kinds of anime videos and films, a user interface design is needed so that website development is easier and can provide user convenience. Good user interface design must be user oriented. This study discusses the design of the user interface on anime streaming websites using the Figma application. The research method used is the prototype method, namely the stage of making the user interface design through a wireframe and then proceed with making a prototype. The finished user interface design will be used as a reference for creating an anime streaming website which will be used as the final product as the output of this research. Based on the test results using the Present facility in the Figma application and trials using a browser on a notebook device, the user interface design of the anime streaming website can run smoothly and the display of all web pages and menu buttons works well. Keywords: Figma, prototype, user interface, website, wireframe